2016
DOI: 10.1016/j.jep.2015.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of safety of modified-Danggui Buxue Tang in rodents:immunological, toxicity and hormonal aspects

Abstract: The present investigation demonstrated that RRF possessed appreciable immunopotentiating activity and had a relatively wide margin of safety. Long-term treatment of RRF exhibited estrogenic properties, and retarded certain age-associated degenerations. RRF might have the potential for further development as a safe and effective alternative/complementary to conventional medication in relieving perimenopausal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The organ index is an essential indicator in toxicity assessment, as the liver and kidneys are the primary organs exposed to potential toxicity. 51 The hearts, livers, spleens, stomachs, and kidneys of the mice in each group were visually examined after dissection, and no abnormalities were observed. Organ weights and organ indices are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The organ index is an essential indicator in toxicity assessment, as the liver and kidneys are the primary organs exposed to potential toxicity. 51 The hearts, livers, spleens, stomachs, and kidneys of the mice in each group were visually examined after dissection, and no abnormalities were observed. Organ weights and organ indices are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…As an important derivative of cholesterol, steroids play an active role in regulating the water-salt balance, stress response, metabolism, and in maintaining sexual differentiation ( Schiffer et al, 2019 ). When Xie et al ( Xie et al, 2016 ) studied the perimenopausal syndrome caused by estrogen deficiency, he found that the modified Danggui Buxue Decoction composed of DG, HQ and Herba Epimedii could significantly alleviate the disorder of steroid hormone metabolism in rat serum. Studies suggested that DBD can play the role of estrogen, and the effect of alleviating menopausal syndrome is mainly caused by the calycosin in HQ ( Gong et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In most of the included studies, the patients were aged 40–60 years and they were administered daily AM and AS at the respective weights of 30 g and 6 g or more. In general, AM and AS exhibit a wide margin of safety [ 58 ], which might explain the lack of an absolute dose range or the ratio of this folk formula for better treatment. Hence, although the literature lacks the clinical evidence regarding the relationship between the dose of DBT and its efficacy, we recruited healthy male volunteers aged 20–30 years and chose to administer DBT with the original dose that has been mentioned since ancient times to minimise the possible adverse effects and individual differences.…”
Section: Discussionmentioning
confidence: 99%